Choro cantado:características interpretativas da voz no gênero - Silva, Andiara Maria Moreira (2020)
The aim of this work is to present the vocais caractheristics of the sung choro. In order to accomplish that, I decided to approach them by making a digression not only into time but also into the ancestrais rhythms that gave rise to it. As it was instrumental, a sung way was paved for given such condition. After taking this pratice to the radio and record companies, a material of big technical challenges, served as a tool for teaching and learning the sung genre. The mentioned recordings were quite useful for this research, dueto the type of analysis made, through listening to selected performances which are called aural analysis. The research also has a study of three cases, where through a semi-structured interview, I was able to collect extremely important data, which could be used to answer my research problem: How is the voice characterized in the sung choro? By seeking to investigate how the contact with given genre took place in the lives of these singers, the technical challenges that this repertoire brought to their study practices, either formal or informal, and how the sung choro reflected in their professional lives individually and in a collective way. To conclude, the present research observed that the voice in choro is characterized by the ability to perform the following aspects: respiratory control, diction, articulation, agility, precise tuning, vocal emission and a good auditory perception.